Identificação de áreas preferenciais para uso de espécies florestais potenciais em sistemas agroflorestais no Arco Verde Paraense - ANDRADE, Daniele Bonente Melo de (Universidade Federal do Pará, 2015)
Deforestation is an evident process at Amazonia from the predatory human activity of natural resources. Logging and agriculture are the main activities that have promoted destruction of forest at Arc of Desforestation. Therefore reforestation has been the focus of public policies that the Government has developed through the “Programa Arco Verde”. In Pará this program is being implemented in 16 municipalities that they constitute the critical areas of deforestation due to human pressures. In this context agroforestry has been an alternative for reforestation these areas. This work aimed identification preferred areas for plantation of 15 tree species with potential use in agroforestry systems. From the intersection of spatial data type of climate and water deficit, we identified 24 bioclimate areas at “Arco Verde” of Para state. The results for plantation of forest species in preferred areas are: J. copaia, T. serratifolia e B. excelsa are potential to be planted 100% do Arco Verde Paraense; C. pentandra, H. courbaril, S. morototoni e T. vulgaris are indicated to be planted in 98% of the target area; C. odorata, C. goeldiana, D. odorata, S. macrophylla are indicated to be insertion in 75% of the “Arco Verde paraense”; C. guianensis, S. parahyba var. amazonicum, B. guianensis e V. maxima in 60% of the area of work. In conclusion, it is necessary further studies in forest species that are suitable for wider preferred areas.